Legal Responses to Violence against Medicare Service Persons and Institutions during COVID- 19 Pandemic in India (Bangladesh Journal of Medical Science, 2023)
Background: The COVID-19 pandemic and virility of the violence against medical personnel have been parallel phenomena in Indian public health administration. The safety and security medical and paramedical have been attracting attention for quite a long time. Still, no central legislation has piloted to enhance their therapeutic and surgical acumen in epidemics and pandemics. The health care of the patients and the covenant of Medicare service persons and institutions doctors missed in the myopic perception of the health administration’s tilt towards the criminal administration of justice.Method: The clasping of 125 years of age epidemic control law and 162 years of age criminal statute stinks the Indian feel in the present context.Result: The significant outcome of the COVID-19 pandemic is showcased in the Epidemic Diseases (Amendment) Ordinance, 2020, ensuring harassment-free workplaces for the medical fraternity. The criminal sanction afforded by the 23 state enactments on the protection of medical care personnel and institutions in states in India, but there is no central legislation. Despite the Indian Medical Association’s recommendation for the Protection of Medical Service Persons and Medical Service Institutions (Prevention of Violence and Damage or Loss of Property) Act, 2017, we witnessed Epidemic Diseases (Amendment) Ordinance, 2020 in enhancing the robust workplace for the doctors during the pandemic. The legal strategy camouflaging ‘disaster’ under Section 2 (d) of the Disaster Management Act, 2005 in pandemic and lockdown is sobering but astonishing.Conclusion: The paper locates the legal response to violence against the doctors in the sociology of medicine and medical professions as professional socialization and social system during the COVID-19 pandemic.Bangladesh Journal of Medical Science Vol. 22 No. 04 October’23 Page : 734-742